2012
DOI: 10.7120/09627286.21.2.167
|View full text |Cite
|
Sign up to set email alerts
|

Activity and enrichment use in disabled Asiatic black bears (Ursus thibetanus) rescued from bile farms

Abstract: Physical disability has the potential to impede the use of environmental enrichments in rehabilitation programmes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…Amputees spent half as much time performing locomotor behaviours as non-amputees, and this could be due to a number of reasons. Dallaire et al (2012) found that amputee Asiatic black bears spent less time on their feet, suggesting that standing and walking may be energetically costly for these individuals. In agreement, Houdijk et al (2009) found that human leg amputees consume more energy whilst walking than non-amputees.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Amputees spent half as much time performing locomotor behaviours as non-amputees, and this could be due to a number of reasons. Dallaire et al (2012) found that amputee Asiatic black bears spent less time on their feet, suggesting that standing and walking may be energetically costly for these individuals. In agreement, Houdijk et al (2009) found that human leg amputees consume more energy whilst walking than non-amputees.…”
Section: Discussionmentioning
confidence: 99%
“…Evenness of space use for each bear was assessed using the Shannon index on the number of instances the bear was observed in the different grid sectors. The Shannon index is typically used to classify species diversity, however it has also been successfully used as a measure of space use evenness (Dallaire et al, 2012). A high Shannon index indicated that a bear visited all sectors, spending even amounts of time in each.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations